Sustainability and Academic Libraries. A story from Denmark - Najmeh Shaghaei; Dorch Bertil (Liber Quarterly: The Journal of European Research Libraries)
The University of Southern Denmark has set out its Vision and Strategy and the Library has become an eminent partner in supporting the University in achieving its sustainability ambitions.